Analisis Sosiolinguistik Bilingualisme Arab-Indonesia dalam Channel Youtube Jeda Nulis - Thaariq, M. Ulfat; Pribadi, Moh.; Zidny, Hilman (STAINI Press, 2025)
This study aims to describe the form and function of Arab-Indonesian bilingualism that appears in the Youtube channel Jeda Nulis managed by Habib Ja'far Husein with the main focus on the phenomenon of code switching and code mixing. This study uses a qualitative approach with a descriptive method because the object of study studied is in the form of speech that contains code switching and code mixing. The source of data in this study is speech contained in videos on Habib Ja'far Husein's YouTube channel Jeda Nulis. The data collection techniques used in this study are in the form of observation techniques and recording techniques. The data collection technique is carried out through observation and notes, then analyzed using several stages, namely reduction, presentation, verification, and drawing conclusions. The result of this research is a form of bilingualism that contains code switching and code mixing and its function in speech contained in the videos of the Jeda Nulis youtube channel. This form of bilingualism is used consciously and structurally to support communicative goals, such as strengthening Islamic messages, affirming religious identity, and conveying Islamic concepts in a more substantive and meaningful way.